Evolutionary theory and the creation controversy - Rieppel, Olivier (Heidelberg New York Springer-Verlag Berlin Heidelberg, 2011)
Evolutionary theory addresses the phenomenon of the origin and diversity of plant and animal species that we observe. In recent times, however, it has become a predominant ideology which has gained currency far beyond its original confines. Attempts to understand the origin and historical development of human culture, civilization and language, of the powers of human cognition, and even the origin of the moral and ethical values guiding and constraining everyday life in human societies are now cast in an evolutionary context. In Evolutionary Theory and the Creation Controversy the author examines evolutionary theory from a historical perspective, explaining underlying metaphysical backgrounds and fundamental philosophical questions such as the paradoxical problem of change, existence and creation. He introduces the scientists involved, their research results and theories, and discusses the evolution of evolutionary theory against the background of Creationism and Intelligent Design.
Electronic reproduction.
Keywords: Evolution (Biology); Creationism; Intelligent design (Teleology).; Electronic books